Encouraging prosocial behavior from older adults through robot teleoperation: A feasibility study - Maalouly, Elie; Hirano, Takashi; Yamazaki, Ryuji; Nishio, Shuichi; Ishiguro, Hiroshi (Frontiers in Computer Science, 2023)
Introduction In Japan, the social climate surrounding older adults has gotten worse as a result of the spread of COVID-19 and the growing isolation of older adults who are increasingly unable to engage in prosocial behavior through work and volunteering. This is detrimental to the physical and mental well-being of older adults. The purpose of this study is to look into robot teleoperation for older adults as a viable way to deal with these issues and overcome the barriers preventing older adults from engaging in prosocial behavior. Materials and methods We designed and tested a remote-control approach for dialogue agents that is appropriate for older adults as well as evaluating their impressions in a real-world setting. Twelve older adults participated in experiments in two separate locations, a children's center and the city ward office, where they could remotely teleoperate a robot and have conversations with the visitors. In the city ward office, the older adults had a conversation with the visitors and gave them information and trivia quizzes about the city. In the children's center, older adults had conversations with children regarding their age, family, their likes, and dislikes. A questionnaire and interview were set up after the experiments to understand their impressions of the system and to clarify how older adults feel about certain issues regarding remote-controlled work, starting a new job, social interaction, to what extent have older adults been affected by the pandemic, how and in what ways has it affected their involvement in society, and whether teleoperating a robot can be a suitable approach to encourage prosocial behavior from them through volunteer work and social engagement. Results The results show that older adults have a strong desire to engage in volunteer work, but are hampered mainly by physical isolation resulting from COVID-19 restrictions and their declining physical and mental health. Their impressions of the teleoperation system were highly positive, as they enjoyed having conversations with children through the robot. With this teleoperation system, older adults were able to remote control a robot by themselves without major issues. It made interaction simpler as conversing with children through a robot added a layer of anonymity that allowed older adults to express themselves freely without worrying about how they are perceived by others in public. Discussion Older adults were able to successfully engage in prosocial behavior through remote-controlling a robot. The system seems to be effective at easing the physical barriers preventing older adults from engaging in volunteer work, which have worsened since the spread of COVID-19.